Variation in salivary protein composition related to feeding behavior and its ecological implications - Baptista, E (2012)
As feeding strategies are typical traits reflecting the adaptation of species, studies on the ingestive physiology of the different trophic groups could increase the knowledge on the complex dynamic processes of grazing ecosystems. This article points out the potential of salivary protein profiles for non-invasively and dynamically accessing mammal feeding behaviour. The oral cavity is the part of an animal’s internal medium that first comes into contact with food. Numerous chemical and mechanical receptors in the mouth respond to chemical and physical properties of food and monitor its changes during processing. This leads to the central perception of taste and texture of food, which together with odor are important determinants in the decision for ingesting or not. Saliva plays an important role in the perception of taste and texture sensations: its composition can modulate food perception and can be simultaneously modulated by the type of diet. Differences in food acceptance are common among species of different trophic groups. They are thought to be related to the levels of potentially harmful compounds found in regular diets and to the behavioral and physiological adaptations of animals to these compounds. Concerning plant secondary metabolites (PSMs), such as tannins, salivary proteins are considered one of the animal’s defense mechanisms. Among the tannin-binding salivary proteins, proline-rich proteins are best studied. Their presence in mammalian saliva varies according to species and dietary habits. However, various other salivary proteins may also be involved in diet selection. An extensive and quantitative comprehension of the salivary protein composition is available for humans, only. In the present article we present the state of the art of animal salivary protein research categorized in trophic groups, which are important to define the ecological role of mammals. For example, sheep and goats are two ruminant species, which differ in PSMs intake and salivary proteomes. In accordance to that, mice, having a different digestive morphophysiology, show significant differences in salivary proteomes both in the normal profile and after tannin consumption. Although adaptation to tannins is species-specific, a common feature found is the increase in protein expression levels usually associated with stress situations. The pro and contra of using these data in ingestive behaviour research is also critically assessed